1977
DOI: 10.1098/rsta.1977.0063
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of major impact processes to lunar crustal evolution

Abstract: Large terrestrial impact craters provide structural models for the interpretation, of lunar craters and basins and petrological data for comparison with complex lunar breccias. The terrestrial examples illustrate the mixing processes operative in the production of impact melts and breccias and the considerable volumes of impact melt rocks in large impact craters. Three forms of craters are found on Earth, Moon, Mars and Mercury; Simple bowl-shaped craters (smallest), central uplift, and ring structures (larges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1987
1987
1987
1987

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Corresponding raw ratios are approximately either 1.4 or 2.0. Ratios including rings ranked III and V, as for the least-squares groups described in Section 5.1, have a larger increment, x Impact-driven wave mechanism at penetration 01 excavation stage; Dominantly surficial Boon and Albritton, 1936McCauley, 1968Baldwin, 1963Hartmann and Wood, 1971Van Dorn, 1968Head, 1974, 1977Chadderton et al, 1969Howard et al, 1974Murray, 1980Mackin, 1969Pike, 1981a Grieve et al, 1981Croft, 1981b (1) Terrestrial geologic evidence for structure associated with rings.…”
Section: Statistical Testsmentioning
confidence: 99%
See 2 more Smart Citations
“…Corresponding raw ratios are approximately either 1.4 or 2.0. Ratios including rings ranked III and V, as for the least-squares groups described in Section 5.1, have a larger increment, x Impact-driven wave mechanism at penetration 01 excavation stage; Dominantly surficial Boon and Albritton, 1936McCauley, 1968Baldwin, 1963Hartmann and Wood, 1971Van Dorn, 1968Head, 1974, 1977Chadderton et al, 1969Howard et al, 1974Murray, 1980Mackin, 1969Pike, 1981a Grieve et al, 1981Croft, 1981b (1) Terrestrial geologic evidence for structure associated with rings.…”
Section: Statistical Testsmentioning
confidence: 99%
“…(2) Does not explain basin outer rings slump feature surrounding an initially smaller excavated crater (Table XI: Group A), was one of the earliest ideas to be advanced for the origin of basin rings on the Moon (Mackin, 1969;Gault, 1974;Head, 1974;Dence, 1976Dence, , 1977McCauley, 1977;Melosh and McKinnon, 1978;and Croft, 1981b). The structural hypothesis is based in part on purportedly analogous rim failure evident in smaller lunar and terrestrial complex craters (Dence, 1964;Quaide et al, 1965), although it has yet to be shown that such modest slumping can be scaled directly to basin-sized events.…”
Section: Models Independentofthe~~~d Spacingmentioning
confidence: 99%
See 1 more Smart Citation